Spatial feature and resolution maximization GAN for bone suppression in chest radiographs. (September 2022) - Rani, Geeta; Misra, Ankit; Dhaka, Vijaypal Singh; Zumpano, Ester; Vocaturo, Eugenio
Highlights: Bone shadow suppression proposed in this research is important for reducing the training time and improving the reliability of deep learning based classification models. Bone shadow suppression without distorting the spatial features of an image play an important role in precise training of a deep learning model. GAN based architectures have potential to retain the image quality while reconstruction. Employing task-specific auxiliary loss functions provide an opportunity to optimize the performance of the GAN based architecture. Graphical abstract: Abstract: Background and Objective: Chest radiographs (CXR) are in great demand for visualizing the pathology of the lungs. However, the appearance of bones in the lung region hinders the localization of any lesion or nodule present in the CXR. Thus, bone suppression becomes an important task for the effective screening of lung diseases. Simultaneously, it is equally important to preserve spatial information and image quality because they provide crucial insights on the size and area of infection, color accuracy, structural quality, etc. Many researchers considered bone suppression as an image denoising problem and proposed conditional Generative Adversarial Network-based (cGAN) models for generating bone suppressed images from CXRs. These works do not focus on the retention of spatial features and image quality. The authors of this manuscript developed the Spatial Feature and Resolution Maximization (SFRM) GAN to efficiently minimize the visibility of bones in CXRs while ensuring maximum retention of critical information. Method: This task is achieved by modifying the architectures of the discriminator and generator of the pix2pix model. The discriminator is combined with the Wasserstein GAN with Gradient Penalty to increase its performance and training stability. For the generator, a combination of different task-specific loss functions, viz., L1, Perceptual, and Sobel loss are employed to capture the intrinsic information in the image. Result: The proposed model reported as measures of performance a mean PSNR of 43.588, mean NMSE of 0.00025, mean SSIM of 0.989, and mean Entropy of 0.454 bits/pixel on a test size of 100 images. Further, the combination of δ = 10 4, α = 1, β = 10, and γ = 10 are the hyperparameters that provided the best trade-off between image denoising and quality retention. Conclusion: The degree of bone suppression and spatial information preservation can be improved by adding the Sobel and Perceptual loss respectively. SFRM-GAN not only suppresses bones but also retains the image quality and intrinsic information. Based on the results of student's t -test it is concluded that SFRM-GAN yields statistically significant results at a 0.95 level of confidence and shows its supremacy over the state-of-the-art models. Thus, it may be used for denoising and preprocessing of images.